Multicenter study of preservative sensitivity in patients with suspected cosmetic contact dermatitis in Korea - LEE, Sang S.; HONG, Dong K.; JEONG, Nam J.; LEE, Jeung H.; CHOI, Yun-Seok; LEE, Ai-Young; LEE, Cheol-Heon; KIM, Kea J.; PARK, Hae Y.; YANG, Jun-Mo; LEE, Ga-Young; LEE, Joon; et al. (Journal of dermatology, 2012)
As many new cosmetic products are introduced into the market, attention must be given to contact dermatitis, which is commonly caused by cosmetics. We investigate the prevalence of preservative allergy in 584 patients with suspected cosmetic contact dermatitis at 11 different hospitals. From January 2010 to March 2011, 584 patients at 11 hospital dermatology departments presented with cosmetic contact dermatitis symptoms. These patients were patch‐tested for preservative allergens. An irritancy patch test performed on 30 control subjects using allergens of various concentrations showed high irritancy rates. Preservative hypersensitivity was detected in 41.1% of patients. Allergens with the highest positive test rates were benzalkonium chloride (12.1%), thimerosal (9.9%) and methylchloroisothiazolinone/methylisothiazolinone (MCI/MI) (5.5%). Benzalkonium chloride and chlorphenesin had the highest irritancy rate based on an irritancy patch test performed using various concentrations. Seven of 30 normal subjects had a positive irritant patch reading with 0.1% benzalkonium chloride and eight of 30 normal subjects had a positive irritant patch reading at 4 days with 0.5% chlorphenesin in petrolatum. Although benzalkonium chloride was highly positive for skin reactions in our study, most reactions were probably irritation. MCI/MI and thimerosal showed highly positive allergy reactions in our study. The optimum concentration of chlorphenesin to avoid skin reactions is less than 0.5%.